IMPLICATIONS OF XENOPHOBIA ON AFRICAN UNITY - AGIDI EJIME PALLY, PHD (International Studies Journal)
At the end of apartheid regime, South African Economy became robust, thereby making her a cynosure of other nations especially African Nations. South Africa started to command sphere of influence and became a rallying point in terms of trade, tourism, education, telecommunication and sport for African countries. As a result, nationals of other countries especially Africa, immigrated into South Africa for jobs, entrepreneurship, education, trade among others. This helped to improve the South African economy the more, while immigrants from other countries equally excel in their various endeavours. Consequent to this, South African nationals developed fear and outright dislike for the immigrant nationals resulting to apparent xenophobic aggression. The paper therefore examines the xenophobia aggression in South Africa and its implication for inter relations in Africa. The paper is a qualitative one that relied on secondary source of information and anchored on system theory as its theoretical framework of analysis. The paper is of the belief that the xenophobia aggression in South African is caused by governance failure. The paper is also of the opinion that the xenophobia aggression will alter the inter relations order and the unity in African region. This can further mar the quest for regional integration. The paper therefore recommends among other things that the xenophobia aggression should be control through regional policies via African Union. Also, South Africa government should initiate policies that will discourage her citizens from xenophobia aggressions by providing good governance that would help her come out from economic recession.